Porous Bioactive Prosthesis With Chitosan/Mesoporous Silica Nanoparticles Microspheres Sequentially and Sustainedly Releasing Platelet-Derived Growth Factor-BB and Kartogenin: A New Treatment Strategy for Osteoarticular Lesions - Yuan, Zhiguo; Lyu, Zhuocheng; Zhang, Wei; Zhang, Jue; Wang, You (Frontiers in Bioengineering and Biotechnology, 2022)
Osteochondral lesions represent a major clinical challenge, especially in the elderly. Traditional treatment strategies, such as arthroplasty or tissue engineering, have limitations and drawbacks. In this study, we presented a new treatment concept for the application of an innovative porous bioactive prosthesis with regenerative activity for the treatment of osteoarticular lesions. For regenerative activity, we fabricated chitosan/mesoporous silica nanoparticles (CS/MSNs) composite microspheres via the microfluidic method as a dual-factor carrier for the sequential release of platelet-derived growth factor BB (PDGF-BB) and kartogenin (KGN). We then integrated the factor carrier and a nondegradable polyetheretherketone (PEEK) scaffold through a surface modification technique to construct the porous sulfonated PEEK (SPK) @polydopamine (PDA)-CS/MSNs scaffold. We systematically evaluated the biocompatibility and biofunctionality of the SPK@PDA-CS/MSNs scaffold and implanted the scaffold in an in vivo cartilage defect model in rabbits. These results suggest that the SPK@PDA-CS/MSNs scaffold is biocompatible, promotes cell migration, enhances chondrogenic differentiation of BMSCs in vitro, and promotes cartilage regeneration in vivo. The porous bioactive prosthesis with regenerative activity presented first in this study may comprise a new therapeutic concept for osteoarticular lesions.